Addiction to Social Media Platforms Among Undergraduate Students - Susai Mari; Jannatabi A. Ganjigatti; Divya Tellis; Jeevita; Daniya Grace Jimson; Fiona Babu; Gangamol P. Siju; Janaki G. Haller; Jayalakshmi Nagesh Naik; Jerlin Niveditha K. (International Journal of Community Health Nursing And Practices, 2024)
Social media addiction is characterized by an excessive preoccupation with social media platforms, leading to an inability to control the urge to engage with them, which in turn disrupts various aspects of life. A substantial majority, approximately 90%, of individuals aged 18 to 29 years, utilize some form of social media. Statistics suggest that the global prevalence of social media addiction exceeds 210 million individuals. The study sought to assess the degree of social media addiction among undergraduate students, employing a non-experimental descriptive design. A total of 400 undergraduate students were chosen through convenience sampling from a degree college. The research utilized a demographic questionnaire and the Social Media Addiction Scale–Student Form. Findings indicated that 49% of participants exhibited a moderate to high level of social media addiction, while 63% demonstrated a moderate to very high level of addiction towards virtual information. Notably, significant correlations were observed between social media addiction and factors such as the students' field of study (p = 0.000005) and the amount of time spent on media per day for academic purposes (p = 0.000474). The study concluded that students displayed varying degrees of social media addiction, warranting interventions to regulate their social media usage behaviours.
Keywords: Social media addiction; academic purposes; demographic questionnaire; undergraduate students